Queerness in the work of Leopold von Sacher-Masoch - Amícola, José (Centro Interdisciplinario de Investigaciones en Género. IdIHCS (CONICET - UNLP). Facultad de Humanidades y Ciencias de la Educación, Universidad Nacional de La Plata, 2017)
The present article tries to account for the relevance the figure of Sacher-Masoch has for fields as different as literature, psychoanalysis and gender studies. Sacher- Masoch has begun to be rescued by the French philosophy from the second half of the 20th century, after having enjoyed much popularity a century before. If Sacher-Masoch fell into disrepute by 1890 from the cataloging of certain sexual perversions under one of his surnames, his present importance would seem to go far beyond what the classificatory minds of Richard von Krafft-Ebing has granted him.